At-sea dumping of dredge spoil: an overview of the Australian policy and legislative framework. Issue 2 (3rd April 2017) - Paredes, Samantha; Pascoe, Sean; Coglan, Louisa; Jennings, Sarah; Yamazaki, Satoshi; Innes, James
ABSTRACT: The increase in port development along the Queensland coast, and the associated dredging activity, has led to increased environmental concerns for the health of the Great Barrier Reef (GBR). While such impacts are of particular immediate concern for the GBR region, the issues surrounding dredging and dumping of dredge spoil are common to many other coastal regions in Australia and elsewhere. In this article, we review the current Australian policy and legislation affecting the dumping at sea of dredge spoil and the incentives this creates in terms of minimising damage. We find that the current complex framework may not necessarily provide appropriate incentives to minimise damage once approval has been obtained, although more recent policy interventions may help encourage innovation in more environmentally friendly actions. We also review the potential for other incentive-based management systems to limit environmental damage from dredging, drawing on the experiences in fisheries and marine biodiversity conservation.